PELATIHAN PEMANFAATAN BAHAN BEKAS SEBAGAI MEDIA PEMBELAJARAN BAGI GURU DI PAUD AN’NASAR - risnajayanti, Risnajayanti; Usman, Usman; Hasan Saali, Yunissyah; Selviani, Nagandi; Riani, Riani (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2024)
This community service aims to improve teacher skills and utilize materials used as creative learning media. This community service program involves teachers to facilitate the implementation of effective and quality learning. Use materials to make learning media, such as ice cream sticks, drink bottles, cardboard, paper, etc. This material is used to provide learning media that can be used according to the needs of teachers and students in the environment around the school. For this reason, there is teacher creativity in learning by utilizing used materials. Used materials are no longer used and can be found in the surrounding environment, where they sometimes pile up and are often thrown away or burned. The benefits of used materials include processing or recycling, such as making cardboard with geometric shapes, ice cream sticks with numbers attached to them, drink bottles made with bowling letters, bottle caps that are given various colors, and drink glasses that can be used as containers for entering numbers or letter. The evaluation was carried out to evaluate teachers' knowledge and skills regarding training in making learning media using used materials after the community service program was implemented. The results of this Community Service benefit teachers and students by allowing them to gain knowledge and skills that can be applied to learning by conditioning the surrounding environment. Using the materials used, teachers can increase creativity and skills in designing learning media effectively and with quality.